Floral Volatile Organic Compounds and a List of Pollinators of Fallopia baldschuanica (Polygonaceae) - Anna Jakubska-Busse; Mariusz Dziadas; Iwona Gruss; Michał J. Kobyłka (Insects, 2022)
Fallopia baldschuanica (Polygonaceae) is an Asian plant growing wild in parts of Europe and North and Central America as an introduced taxon, in many countries it is considered a potentially invasive species. This article presents the list of 18 volatile organic compounds (VOCs) emitted by the flowers of F. baldchuanica and identified by headspace gas chromatography/mass spectrometry (HS-GC/MS) analyzes, and a list of flower-visiting and pollinating insects that have been observed in the city center of Wrocław (SW Poland). β-ocimene, heptanal, nonanal, α-pinene, 3-thujene, and limonene, were detected as the floral scent’s most important aroma compounds. F. baldschuanica also produces the aphid alarm pheromones, i.e., β-farnesene and limonene, that repels aphids. Additionally, the pollinators of F. baldschuanica were indicated, based on two years of observations in five sites in the urban area. It was found, that the pollinators of this plant with the highest species stability are: Diptera from families Syrphidae (Chrysotoxum bicinctum, Eristalis pertinax, Eupeodes corollae, Episyrphus balteatus, Eristalis tenax, Syrphus ribesii, Eristalis intricaria), Muscidae (Musca domestica), Sarcophagidae (Sarcophaga spp.), Calliphoridae (Lucilia sericata, Lucilia caesar), Hymenoptera from families Vespidae (Vespula vulgaris), and Apidae (Apis sp., Bombus sp.). The key role of VOCs in adaptation to plant expansion is discussed.